A Method for Assessment and Grading of Osteoarthropathy in Hemophiliacs - Horoszowski, H.; Seligsohn, U.; Heim, M.; Farine, I. (Thrombosis and Haemostasis, 1977)
Neither of the previously described methods for assessment of hemophilic osteoarthropathy has included all aspects, which we deem, are necessary for appropriate evaluation and follow-up of individual joints and the general state of the patient. We devised a simple method, expressed by scores, which differentially assesses the functional, the objective findings and roentgenologic state of the joints. For the last 4 years, we have been using this method in 110 hemophilic patients in Israel and have found it very efficient for: a) Quantitative comparison of the state of different joints in the same patient, b) Comparison of the state of similar joints in different patients, c) Comparison of the general state of different patients, d) Evaluation of the efficacy of treatment. The method can be easily applied by any physician and may provide means of comparing results achieved by various hemophilia centers.